2011
DOI: 10.1094/pdis-01-11-0065
|View full text |Cite
|
Sign up to set email alerts
|

Soil Suppressiveness to Fusarium Disease Following Organic Amendments and Solarization

Abstract: Soil suppressiveness to soilborne pathogens can evolve following the incorporation of plant residues in the soil and solarization. We studied its occurrence by assessing disease incidence and severity in sandy soil which was infested after the disinfestation treatment. Disease incidence and severity of crown and root rot in cucumber plants inoculated with Fusarium oxysporum f. sp. radicis-cucumerinum macroconidia were reduced by 20 to 80% when seedlings were planted in the tested soils 2 to 34 months after soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 45 publications
1
46
1
1
Order By: Relevance
“…The multiple mechanisms involved determine the thermal inactivation of the pathogen due to increased soil temperature (Katan et al, 1976), or the weakening of pathogen propagules that become more susceptible to competition or antagonistic activity of the indigenous soil microflora (Stapleton, 2000). Soil solarization, either alone or combined with organic amendments, and soil flooding, are effective in controlling many soilborne plant pathogens (Katan, 1981;Blok et al, 2000;Klein et al, 2011;Melero-Vara et al, 2011). In addition, soil solarization frequently enhances plant growth by improving soil structure, releasing nutrients (Chen et al, 1991) and stimulating plant growth promoting rhizobacteria (Gamliel & Stapleton, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The multiple mechanisms involved determine the thermal inactivation of the pathogen due to increased soil temperature (Katan et al, 1976), or the weakening of pathogen propagules that become more susceptible to competition or antagonistic activity of the indigenous soil microflora (Stapleton, 2000). Soil solarization, either alone or combined with organic amendments, and soil flooding, are effective in controlling many soilborne plant pathogens (Katan, 1981;Blok et al, 2000;Klein et al, 2011;Melero-Vara et al, 2011). In addition, soil solarization frequently enhances plant growth by improving soil structure, releasing nutrients (Chen et al, 1991) and stimulating plant growth promoting rhizobacteria (Gamliel & Stapleton, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The observed suppressive effects of organic‐farmed soils on bacterial seedling diseases were consistent with our previous report showing the suppressive effect of independent organic‐farmed soils on bacterial rice seedling diseases (Ando et al., ). Various physicochemical or biological properties that have been noted upon the addition of organic amendments to soil could be associated with disease‐suppressive activity (Bonanomi et al., ; Borrero, Trillas, Ordovás, Tello, & Avilés, ; Hoitink, ; Klein et al., ; Steinberg, Edel‐Hermann, Alabouvette, & Lemanceau, ). In our experiments, comparison of the physicochemical properties of organic‐farmed soil with those of commercial conventional soil suggested that many organic‐farmed soils but not all analysed here had higher of CEC value (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Among substitutive chemicals, currently registered alternatives to MB are chloropicrin (CP); 1,3-dichloropropene (1,3-D); methyl isothiocyanate (MITC) generators such as Metam sodium (MNa) and Dazomet (DZ), abamectin (AB) and their combinations (Qiao et al, 2012;Mao et al, 2012;Yan et al, 2012). Other alternatives to MB fumigation may be the use of non-chemical methods, such as soil solarization, organic amendments and biocontrol agents (Klein et al, 2011;Caboni et al, 2013;Hu et al, 2013). However, nonchemical control methods alone are often unsuitable because they do not provide the broad-spectrum activity or the degree of consistency achieved with MB fumigation (Chellemi, 2002).…”
Section: Introductionmentioning
confidence: 99%